RNA-Mediated Control in Listeria monocytogenes: Insights Into Regulatory Mechanisms and Roles in Metabolism and Virulence - Krawczyk-Balska, Agata; Ładziak, Magdalena; Burmistrz, Michał; Ścibek, Katarzyna; Kallipolitis, Birgitte H. (Frontiers in Microbiology, 2021)
Listeria monocytogenes is an intracellular pathogen that is well known for its adaptability to life in a broad spectrum of different niches. RNA-mediated regulatory mechanisms in L. monocytogenes play important roles in successful adaptation providing fast and versatile responses to a changing environment. Recent findings indicate that non-coding RNAs (ncRNAs) regulate a variety of processes in this bacterium, such as environmental sensing, metabolism and virulence, as well as immune responses in eukaryotic cells. In this review, the current knowledge on RNA-mediated regulation in L. monocytogenes is presented, with special focus on the roles and mechanisms underlying modulation of metabolism and virulence. Collectively, these findings point to ncRNAs as important gene regulatory elements in L. monocytogenes, both outside and inside an infected host. However, the involvement of regulatory ncRNAs in bacterial physiology and virulence is still underestimated and probably will be better assessed in the coming years, especially in relation to discovering the regulatory functions of 5′ and 3′ untranslated regions and excludons, and by exploring the role of ncRNAs in interaction with both bacterial and host proteins.